A modified PID-based control scheme for depth-of-hypnosis control: Design and experimental results. (June 2022) - Schiavo, Michele; Padula, Fabrizio; Latronico, Nicola; Paltenghi, Massimiliano; Visioli, Antonio
Highlights: A PID-based control system for general anesthesia is considered. Depth-of-Hypnosis is controlled by propofol and remifentanil coadministration. A suitable bolus is used in the induction phase. A nonzero baseline infusion is used in the maintenance phase. Experiments show there are significant advantages from a clinical standpoint. Abstract: Background and Objective: Many methodologies have been proposed for the control of total intravenous anesthesia in general surgery, as this yields a reduced stress for the anesthesiologist and an increased safety for the patient. The objective of this work is to design a PID-based control system for the regulation of the depth of hypnosis by propofol and remifentanil coadministration that takes into account the clinical practice. Methods: With respect to a standard PID control system, additional functionalities have been implemented in order to consider specific requirements related to the clinical practice. In particular, suitable boluses are determined and used in the induction phase and a nonzero baseline infusion is used in the maintenance phase when the predicted effect-site concentration drops below a safety threshold. Results: The modified controller has been experimentally assessed on a group of 10 patients receiving general anesthesia for elective plastic surgery. The control system has been able to induce and maintain adequate anesthesia without any manual intervention from the anesthesiologist. Conclusions: Results confirm the effectiveness of the overall design approach and, in particular, highlight that the new version of the control system, with respect to a standard PID controller, provides significant advantages from a clinical standpoint.